Perbandingan Pengaruh Latihan Plyometric Squat Jump dan Hexagon Jump terhadap Power Otot Tungkai Atlet Remaja Sepak Bola - Ahmad Naufal; Himawan Wismanadi (Mutiara Pendidikan dan Olahraga, 2025)
In modern soccer, lower-limb power is a crucial component that determines an athlete’s performance in sprinting, kicking, and jumping. This study aimed to compare the effects of Squat jump and Hexagon jump plyometric exercises on lower limb power in youth soccer athletes from Garuda Timur Football Academy Surabaya. The research employed a quasi-experimental method with a pretest–posttest two group design involving 12 athletes aged 14–17 years. Participants were divided into two groups of six: a Hexagon jump group and a Squat jump group. Lower limb power was assessed using the vertical jump test before and after the training intervention. Data were analyzed using the Matched Subject Ordinal Pairing (MSOP) method to determine the relative effectiveness of both training types. The results indicated that both exercises significantly improved athletes’ vertical jump performance. However, the Hexagon jump exercise showed greater effectiveness, with a winning proportion of 67% (4 out of 6 pairs) compared to 33% for the Squat jump. The superior results of the Hexagon jump group were attributed to its multidirectional movement pattern, which provides greater stimulation of coordination, balance, and neuromuscular reactivity. Therefore, it can be concluded that Hexagon jump training is more effective than Squat jump in enhancing lower limb power among youth soccer athletes.